Spatial Variations in Magmatic Volatile Influx and Fluid Boiling in the Submarine Hydrothermal Systems of Niuatahi Caldera, Tonga Rear‐Arc. (13th April 2022) - Falkenberg, Jan J.; Keith, Manuel; Haase, Karsten M.; Sporer, Christian; Bach, Wolfgang; Klemd, Reiner; Strauss, Harald; Storch, Bettina; Peters, Christian; Rubin, Kenneth H.; Anderson, Melissa O.
Abstract: Submarine caldera volcanoes may host several hydrothermal systems along the caldera wall and related to volcanic cones. Fluid boiling and magmatic volatile influx are common processes in shallow (<2, 000 mbsl) subduction zone‐related environments causing variations in the mineralogical and chemical composition of seafloor hydrothermal mineralizations that remain poorly constrained. The submarine caldera of Niuatahi volcano, Tonga rear‐arc, hosts four active vent sites discharging high temperature fluids (<334°C) with variable salinities (369–583 mM Cl) that are indicative of fluid boiling, recorded by distinct Te/As and Te/Au in pyrite, sphalerite, and chalcopyrite. High sulfidation mineral assemblages (e.g., enargite), stable S isotope data and similar trace element signatures in sulfides and native S condensates suggest a minor and/or infrequent contribution of magmatic SO2 to the hydrothermal systems located proximal to the caldera center causing a volatile element (e.g., Se, Bi, Te) enrichment. The hydrothermal system at the northern caldera wall is decoupled from the magmatic SO2 source, as revealed by radiogenic Pb isotopes. Instead, S isotope and trace element constraints propose a host rock‐dominated hydrothermal system, lacking a magmatic volatile influx. The observed hydrothermal fractionation processes (fluid boiling) and the distinct metal (loid) sources (magmatic volatiles vs. host rock) represent a continuum from magmatic volatile‐ to host rock‐dominated hydrothermal systems within the Niuatahi caldera. This leads to seafloor mineralizations with spatially selective trace element enrichments, like Te, Se, and Bi (±Au, Ag) in the caldera center compared to Au, Ag, Zn, Cd, and Pb at the northern caldera wall. Plain Language Summary: Seafloor mineralization (e.g., black smokers) with different compositions can occur at hot springs at submarine caldera volcanoes associated with volcanic cones or the caldera wall. The effect of boiling fluids and the addition of magmatic gases results in local differences in the metal budget in the related hydrothermal sulfide minerals, which are poorly constrained. The Niuatahi volcano in the western Pacific is such an example, where four different hot springs are discharging up to 334°C hot fluids with variable salt and metal contents. The trace element and isotope composition of hydrothermal sulfide minerals agree with the hot fluid composition and indicate that fluid boiling at the caldera center is a common process, alongside the influx of magmatic gases, which drastically enhances the metal budget of the mineralization. By contrast, metal transfer due to magmatic gas is not evident in the hot springs at the northern caldera wall, which is rather controlled by evolved seawater and fluid interaction with the surrounding rocks. The observed chemical variations show that Niuatahi caldera is host to a continuum from magmatic gas‐rich to host rock‐controlled hydrothermal systems, which ultimately results in seafloor mineralization that exhibit spatially selective trace element enrichments. Key Points: Niuatahi rear‐arc caldera is host to a metallogenic continuum of magmatic volatile‐ to host rock‐dominated mineralization Variable proportions of magmatic volatile influx and fluid boiling result in spatially selective trace element enrichment (Te, Se, Bi) Fluid boiling and magmatic volatile input is recorded by distinct Te/As, Te/Au, and low δ 34 S values in hydrothermal sulfides and native S